How the EU’s Eastern Enlargement Changed the German Productive Model. The Case of the Automotive industry - Martin Krzywdzinski (Revue de la Régulation)
What impact did the Eastern Enlargement of the European Union have on the productive models and labor relations in the German automotive industry? Did it lead to a “race to the bottom” and “social dumping”? This article examines the evolution of value chains and product strategies as well as the development of employment and labor relations in the German automotive industry and discusses the hypotheses of “dualization” or “disintegration.” It is based on case studies of automobile manufacturers and suppliers as well as on statistical data about employment, foreign trade, and foreign direct investment. The analysis shows that the use of low-cost locations in CEE allowed German automotive companies to strengthen their focus on high-quality products without losing their price competitiveness. German companies have used relocation threats to demand labor cost reductions and higher flexibility on working times and employment (i.e., the use of agency work) in their home country locations. These demands, however, did not go as far as to break the governance compromises in the German automotive industry. The metalworking union and the works councils still remain strong enough to reach compromises that guarantee employment security in exchange for higher flexibility and that set limits on the use of precarious employment forms.